Investigation of Soft Stories in Buildings with Hollow Block Slab - Ince, Ozan; Sahin, Humeyra; Alyamac, Kursat Esat; Ulucan, Zulfu Cinar (Fırat University, 2018)
Hollow block slab is a floor slab system that consists of a thin slab and joists. In hollow block slab system, nonstructural materials are used between joists. Hollow block slab usually consists of wide and shallow beams. Because of low beam height in this system, its lateral stiffness is less than beam floor systems. Because hollow block slab has low lateral stiffness, using of this slab type increases soft-story risk in buildings that have soft-story risk. Therefore, in building with hollow block slab should be detailedly investigated regarding soft-story. For this reason, in this study buildings with stores of 5, 8 and 11, which constructed with hollow block slab were numerically investigated for different ground story height. According to analysis, lateral drift ratios was obtained for each story. As ground story height increased, the lateral drift ratios of ground story with hollow block slab were increased nearly between 33% and 50%. As the number of stories increased, the lateral drift ratios have approached upper limit which is recommended by TEC-2007. The high values of lateral drift ratios in ground stories increase soft-story risk. This situation has a negative effect on building performance under lateral loads. For improving this negative effect shear walls was added to the systems and analysis was repeated. Because shear walls have decreased lateral drift ratios of ground stories nearly between 40% and 60%, negative effect of increment in ground story was decreased. It is agreed on that in high seismic zone, buildings with hollow block slab should be designed as a frame-wall system for better building performance.
Keywords: Engineering; Mühendislik